Tamoxifen Inhibits TGF‐β‐Mediated Activation of Myofibroblasts by Blocking Non‐Smad Signaling Through ERK1/2. Issue 12 (24th August 2015) - Carthy, Jon M.; Sundqvist, Anders; Heldin, Angelos; van DAM, Hans; Kletsas, Dimitris; Heldin, Carl‐Henrik; Moustakas, Aristidis
<x xml:space="preserve">Abstract</x> Transforming growth factor‐β (TGF‐β) is a multifunctional cytokine which stimulates the differentiation of fibroblasts into myofibroblasts. Myofibroblasts are critical for normal wound healing, but also accumulate pathologically in a number of chronic inflammatory conditions where they are key contributors to aberrant tissue remodeling and fibrosis, and in cancer stroma. In the current study, we identified a role for tamoxifen as a potent inhibitor of the TGF‐β‐mediated activation of primary human skin and breast fibroblasts. Our data indicate that tamoxifen does not interfere with canonical Smad signaling downstream of TGF‐β but rather blocks non‐Smad signaling through ERK1/2 MAP‐kinase and the AP‐1 transcription factor FRA2. We further demonstrate by siRNA‐mediated knockdown that FRA2 is critical for the induced expression of myogenic proteins in response to TGF‐β. Functionally, TGF‐β‐stimulated fibroblast‐mediated contraction of collagen gels was impaired in the presence of tamoxifen. Altogether, these data demonstrate that tamoxifen prevents myofibroblast differentiation and, therefore, may provide therapeutic benefits to patients suffering from chronic inflammatory conditions or cancer. J. Cell. Physiol. 230: 3084–3092, 2015. © 2015 Wiley Periodicals, Inc.